Risk Estimation of Aortic Stiffness in Patients with End Stage Renal Disease on Maintenance Haemodialysis (BIRDEM Medical Journal, 2019)
Background: The stiffness of the large elastic arteries increase the morbidity and mortality. The purpose of the present study was to estimate the risk of aortic stiffness among end stage renal disease patients on maintenance haemodialysis.Methods: This cross-sectional study was carried out in the Department of Nephrology at National Institute of Kidney Diseases and Urology (NIKDU), Dhaka and National Institute of Cardiovascular Disease and Hospital (NICVD), Dhaka, Bangladesh from January 2013 to December 2014 for a period of two years. Chronic kidney disease in stage 5 [CKD-5(D)] patients older than 18 years on maintenance haemodialysis (MHD) for more than 3 months were designated as case group and age and sex matched non CKD patients were considered as control group. Serum calcium, serum albumin, serum phosphate and iPTH were estimated by semi-automated biochemistry analyzer from the Department of Biochemistry of NIKDU, Dhaka and NICVD, Dhaka. Plain Xray abdomen in lateral view was performed for all patients.Result: A total number of 100 patients were enrolled for this study of which 50 patients were in end stage renal disease (ESRD) group and the rest 50 patients were in non-CKD group. Mean (±SD) aortic stiffness index was significantly higher (P